2013
DOI: 10.1021/am402778u
|View full text |Cite
|
Sign up to set email alerts
|

Pentacene on Ag(111): Correlation of Bonding Distance with Intermolecular Interaction and Order

Abstract: We report coverage and temperature dependent bonding distances of vacuum-sublimed pentacene (PEN) submonolayers on Ag(111) obtained by the X-ray standing wave technique. The average vertical bonding distance of 2.98 Å at room temperature for 0.50 monolayer (ML) coverage increases to 3.12 Å for 0.75 ML due to competing intermolecular and adsorbate-substrate interactions. In contrast, decreasing the temperature from 295 to 145 K does not impact the bonding distance despite the concomitant transition from a "liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 55 publications
(128 reference statements)
8
52
0
Order By: Relevance
“…Both PBE and PBE+vdW surf , however, predict flat conformation for pentacene/Ag(111), as can be seen in Fig. 6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 88%
See 1 more Smart Citation
“…Both PBE and PBE+vdW surf , however, predict flat conformation for pentacene/Ag(111), as can be seen in Fig. 6, in agreement with experimental observations 10,45,46 . Our results are also in good agreement with previous theoretical studies: from PBE calculations we found d = 3.938Å and E ads = −0.119 eV, which compare well with previous GGA results (d = 3.7-4.12Å and E ads within the range of −0.078 to −0.108 eV) 47,48 ; using the PBE+vdW surf method we found d = 2.910Å and E ads = −2.396 eV, which is in good agreement with previous results obtained by Toyoda et al 47 using the pairwise DFT-D method (d = 2.9Å and E ads = −2.28 eV), but differ from the values obtained by the same authors using the nonlocal vdW-DF method (d = 3.7Å and E ads = −1.62 eV) 47 .…”
Section: B Pentacene On Ag(111)supporting
confidence: 88%
“…Experimental studies have reported that both anthracene and pentacene monolayers weakly adsorb on Ag(111), as characteristic of physisorption or weak chemisorption [5][6][7][8][9][10] , which suggests that van der Waals interactions (vdW) play an important role in the binding of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have seen examples in which the acceptor character of a molecule causes Δ to reverse its sign, e.g., FTCNQ/Cu(111) . Another reason for the differences between fluorinated and non‐fluorinated molecules in Table is the generally larger adsorption height of the former . A larger adsorption height means a reduced push‐back effect, and therefore a smaller Δ value.…”
Section: Binary Layers On Metal Surfacesmentioning
confidence: 98%
“…Like countless other systems, CuPc, PEN and their fluorinated counterparts form ordered single‐component monolayers on Au(111), Ag(111) and Cu(111). All these layers have been structurally and electronically characterized in the past decade. We are mainly interested in interfacial electronics.…”
Section: Binary Layers On Metal Surfacesmentioning
confidence: 99%
“…In contrast, very good agreement between theory and experiment is achieved for model 1. Two aspects deserve special attention: First, the larger P H,C core for sample B than samples A and C can be rationalized by an increased intermolecular interaction at the larger PTCDI coverage in this case [29], a correlation that was reported for pentacene on Ag(111) [42]. In contrast, the OH depletion of the surface of sample C has no apparent effect on the adsorption distances that could, in turn, be related to terminating OH.…”
mentioning
confidence: 88%